A COMPREHENSIVE STUDY OF SOFTWARE PREFERENCES AMONG UiTM CIVIL ENGINEERING STUDENTS AND IMPLICATIONS FOR BIM EDUCATION - Mohd Azrizal Fauzi; Ezliana Ghazali; Muhamad Faizal Pakir Mohamed Latiff; Zulfairul Zakariah, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This comprehensive study investigates the software preferences of civil engineering students at Universiti Teknologi MARA (UiTM) in Malaysia, focusing on the adoption of Building Information Modeling (BIM) and traditional Computer-Aided Design (CAD) software. The research specifically delves into student preferences regarding the top 10 BIM software for civil engineers, explores factors influencing their choices, identifies perceived benefits and barriers to BIM adoption, and provides recommendations for curriculum development to bridge the gap between theoretical knowledge and practical BIM application. A mixed-methods approach was employed, encompassing surveys, semi-structured interviews, and focus group discussions to gather data from a large sample size of students. Results reveal a predominant preference for CAD software, particularly AutoCAD, due to its familiarity, ease of use, and prior exposure. However, students acknowledged the potential benefits of BIM, such as improved collaboration, enhanced visualization, and reduced errors. Key barriers to BIM adoption included limited access to software, inadequate training, and concerns about industry readiness. The study emphasizes the need for educational institutions to comprehensively integrate BIM into the curriculum, provide hands-on training with industry-standard software, and foster collaboration with industry partners to ensure future civil engineers are equipped for the digital transformation of the construction industry. The findings offer valuable insights for stakeholders invested in cultivating a BIM-ready workforce in Malaysia.